Mediation of JA signalling in glandular trichomes by the woolly/SlMYC1 regulatory module improves pest resistance in tomato. Issue 2 (20th September 2020) - Hua, Bing; Chang, Jiang; Wu, Minliang; Xu, Zhijing; Zhang, Fanyu; Yang, Meina; Xu, Huimin; Wang, Ling‐Jian; Chen, Xiao‐Ya; Wu, Shuang
Summary: Almost all plants form trichomes, which protect them against insect herbivores by forming a physical barrier and releasing chemical repellents. Glandular trichomes produce a variety of specialized defensive metabolites, including volatile terpenes. Previous studies have shown that the defence hormone jasmonic acid (JA) affects trichome development and induces terpene synthases (TPSs) but the underlying molecular mechanisms remain unclear. Here, we characterized a loss‐of‐function allele of the HD‐ZIP IV transcription factor woolly ( wo ) and analysed its role in mediating JA signalling in tomato. We showed that knockout of wo led to extensive trichome defects, including structural and functional changes in type VI glandular trichomes, and a dramatic reduction in terpene levels. We further found that wo directly binds to TPS gene promoters to recruit SlMYC1, a JA signalling modulator, and that together these transcription factors promote terpene biosynthesis in tomato trichomes. The wo/SlMYC1 regulatory module is inhibited by SlJAZ2 through a competitive binding mechanism, resulting in a fine‐tuned JA response in tomato trichomes. Enhanced expression of SlMYC1 substantially increased terpene levels and improved tomato resistance to spider mites. Interestingly, we also found that SlMYC1 plays an additional role in glandular cell division and expansion in type VI trichomes, independent of JA. Together, our results reveal a novel, JA‐mediated regulatory mechanism that promotes insect resistance in tomato.